Imidazole and its derivatives as potential candidates for drug development - Mumtaz, Amara; Saeed, Aamer; Fatima, Nighat; Dawood, Muhammad; Rafique, Hummera; Iqbal, Jamshed (Bangladesh Journal of Pharmacology, 2016)
Imidazole and its derivatives are the pharmacological significant scaffolds with the broad spectrum of activities can be synthesized in the laboratory in the single step by the action of the catalyst. The current review summarizes the role of the imidazole and its derivatives during the last decade (2005-2014) for the treatment of many diseases. Review highlights their significant contribution towards the drug development for the treatment of some fatal diseases like HIV, cancer, tuberculosis and hepatitis C. As imidazole and its derivatives continue to play an important role for the treatment of many diseases so there is a need to trigger research in this field.